Comparison of Structured Clinical Instruction Module and Video-Assisted Instructor -Led Training in Accelerating and Retention of Nursing and Midwifery Students' Skill in Neonatal Resuscitation - Fatemeh Erfanian Arghavanian; Javad Malekzadeh; Gholam Ali Mamouri; Talat Khadivzadeh (Mashhad University of Medical Sciences, 2023)
Background & aim: Some studies have called into question medical students' competency in neonatal resuscitation. Therefore applying standard training methods has been recommended. This study compared the effect of Structured Clinical Instruction Module (SCIM) and video-assisted Instructor -led training (ILT) in accelerating and retention of students' knowledge and skill in neonatal resuscitation.Methods: In this experimental study 48 nursing and midwifery students of Mashhad University of Medical Sciences, Mashhad Iran, who did not attended in any related education, were allocated in SCIM, VT and control group through stratified randomization. In SCIM group, after lecture, six groups of students rotated through six stations, trained and practiced under supervision of six instructors.  In VT group after lecture an instructional video presented then students repeated the video and discussed its content with each other and instructor. Before, after and one month following workshops all students participated in an OSCE to assess their cognitive, technical and behavioral skills. Paired t-test and One-way ANOVA were used for data analysis.Results: In post-test, both groups of SCIM and VT had better performance than control group (p<.001, p<.001, respectively). But SCIM group demonstrated a marked improvement compared with VT group (202.97±16.6 vs 173.6±15.3 (P<0.001). There was a significant difference between students' comfort and confidence in both SCIM and VT groups (P<0/001). In retention test total score between three groups showed significant difference (P<0.001); whilst the SCIM group had significantly better performance (P<0.001).Conclusion: SCIM is an effective method in acquisition and retention of neonatal resuscitation skill. So its application is recommended in the neonatal resuscitation training.